2007
DOI: 10.1016/j.cardiores.2006.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Genetic deficiency of cyclooxygenase-2 attenuates abdominal aortic aneurysm formation in mice

Abstract: Our findings suggest that increased COX-2 expression in smooth muscle cells of the abdominal aorta contributes to AAA formation in mice by enhancing inflammatory cell infiltration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
72
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(75 citation statements)
references
References 43 publications
(68 reference statements)
2
72
0
1
Order By: Relevance
“…37,54 Our results demonstrating that an increase in COX-2 expression in Ang IIeinduced AAA in Apoe À/À /Cyp1b1 þ/þ mice was prevented by TMS or Cyp1b1 gene disruption suggests that CYP1B1 acts upstream of COX-2 in minimizing AAA, which could be due to ROSs generated by CYP1B1. Supporting this view was our finding that the administration of tempol attenuated the expression of COX-2, which could occur via p38 MAPK, as reported in previous studies.…”
Section: Discussionmentioning
confidence: 86%
“…37,54 Our results demonstrating that an increase in COX-2 expression in Ang IIeinduced AAA in Apoe À/À /Cyp1b1 þ/þ mice was prevented by TMS or Cyp1b1 gene disruption suggests that CYP1B1 acts upstream of COX-2 in minimizing AAA, which could be due to ROSs generated by CYP1B1. Supporting this view was our finding that the administration of tempol attenuated the expression of COX-2, which could occur via p38 MAPK, as reported in previous studies.…”
Section: Discussionmentioning
confidence: 86%
“…3 Inflammatory cells produce proinflammatory cytokines and interlace an inflammatory network, which may contribute to tissue destruction and weakened arterial wall. 4 Matrix metalloproteinases (MMPs), expecially MMP-2 and MMP-9, the predominant proteinases in the aortic wall, degrade the extracellular matrix (ECM) and are thought to play a key role in AAA formation. 5 Experimental evidence has emerged that defective inflammation and inhibition of MMP activity may attenuate aneurysm formation in animal models.…”
mentioning
confidence: 99%
“…Moreover, Ang II may stimulate the expression of cyclooxygenase-2 (COX-2) [42,43], a critical enzyme in AAA pathogenesis that forms vasoactive and inflammatory prostaglandins. Indeed, it has been shown that COX-2 deficiency attenuates Ang II infusion-mediated dissecting AAA [44]. Ang II also may stimulate osteopontin (OPN) secretion and actions [45].…”
Section: Renin Angiotensin System -Classical Systemmentioning
confidence: 99%